Ketoconazole Inhibits Ovulation as a Result of Arrest of Follicular Steroidogenesis in the Rat Ovary - Michael Gal; Joseph Orly (SAGE Publishing, 2014)
Objective Ketoconazole (KCZ) is a known inhibitor of steroidogenic P450 enzymes in the adrenal cortex and the gonads. Previous studies examined the potential clinical use of KCZ for attenuation of ovarian response to gonadotropin treatments. This study aimed to use the superovuating rat model to explore the effect of KCZ on ovarian steroidogenesis, follicular function, and development toward ovulation. Methods Prepubertal rats were treated with equine chorionic gonadotropin (eCG)/human CG (hCG) resulting in multiple follicular development and ovulation. The effect of KCZ on this model was examined by administration of KCZ-gel formula and subsequent analyses of ovarian steroidogenesis, rate of ovulation, morphometric assessments of follicular parameters, and cell-specific steroidogenic maturation of the treated ovaries. Results When applied shortly before gonadotropin stimulation, KCZ markedly reduced ovarian progesterone, androstenedione, and estradiol levels down to 18.7, 36.5, and 19.0%, respectively ( P < 0.001). A single KCZ-gel administration of 6, 12, and 24 mg/rat resulted in reduction of ovulated ova/ovary down to 8.6 ± 4.9, 5.1 ± 4.3, and 2.4 ± 3.2, respectively, as compared to 13.6 ± 4.4 ova found in the oviduct of control-gel-injected animals ( P < 0.001). An alternative protocol made use of small KCZ doses injected in non-gel formula (5 mg/dose/8 hours), commenced with the eCG administration and terminated 24 hours later; this treatment readily inhibited the ovulation rates to 6.6 ± 6.6 as compared to 16.5 ± 4.1 ova/ovary in the control group ( P < 0.01). By contrast, KCZ failed to inhibit ovulation if administered 24 hours after eCG injection. Anovulation by KCZ resulted from arrest of follicular development at the stage of 800-840 μm Graafian follicles as compared to 920 μm of peri-ovulatory follicles (OFs) observed in the control group, P = 0.029. In addition, absence of CYP11A1 expression was evident in the granulosa cell layers of the growth-arrested follicles, which also lacked mucified mature cumulus cell complexes. Conclusion These results suggest that KCZ-mediated inhibition of follicular maturation probably results from impaired steroidogenesis at early phase of follicular development toward ovulation. Hence, attenuation of folliculogenesis by KCZ may be harnessed to modulate gonadotropin-ovarian stimulation in fertility treatments.